EVALUATING THE ROLE OF THE USAID IN COMMUNITY BASED SOLID WASTE MANAGEMENT (CBSWM) PROGRAM - Prasetyanti, Retnayu (JURNAL MANAJEMEN DAKWAH, 2015)
The existence of international actor has become hot issue in this globalization world. Community Based Solid Waste Management (CBSWM) program is one of the commitment of The United States Agency for International Development (USAID) in helping Indonesian government reducing the environmental problems, particularly the problem of waste. Just like another program that is needed to be evaluated and improved, CBSWM also has big attention from public community. The real role of USAID in CBSWM raised a lot of question relates to the success of the program. Many people said agree to the effective role of USAID, and so does the program of CBSWM. The core point to understand the role of USAID is consisted to two urgent questions about the perspective of the program implementation and also the impact that community felt. These two perspectives are the main measurement tool to assess the role of USAID and its key learning of success. While in this research, the quantitative approach the researcher used is Analysis of Variance (ANOVA); it is a technique to test a similarity of mean of the variable in the same time. After that, the analysis of the role of USAID in CBSWM will be derived in theoritical explanation on the sound governance and community empowerment perspective. From this result, the role of USAID was really good in the process of implementation and given good impact to the environmental condition, activity and facility. The failure on the aspect of community welfare does not make a complex problem since the main purpose of the program is in the context of environment. The success of CBSWM program not only comes from the serious role of USAID, it needs community and government total support. Local government and community need to hold a closer partnership to maximize the result USAID has achieved and to make a better condition of community welfare. A good quality life of community will determine a good condition of environment. Keywords: Globalization, International Actor, USAID, Sound Governance, Community Empowerment